"Do You Guys Take Showers with Your Children?": Gendered Embodiment and the Legitimation of Italian Fathering Practices. (June 2021) - Mercuri, Eugenia
This work aims at investigating gendered embodiment in fathering practices in a national context, Italy, where understandings of fatherhood, at the institutional as well as the individual level, are still more centered on the provider ideal than on a model of nurturing and caring fatherhood. This qualitative research on Italian first-time fathers of children under three years of age focused on men's participation in routine, instrumental, and material childcare practices, exploring the potential for a transformation in both the meanings attached to fatherhood as well as to aspects related to embodiment and constructions of masculinity that sustain inequalities. The findings show that, while participation in hands-on childcare plays an important role in the construction of intimate father-child relationships, a legitimation of men's bodies' involvement in interaction with children is still missing, especially for care practices that overlap with constructions of motherhood.